Effect of the stress state on the adhesive strength of an epoxy-bonded assembly - Sergey Smirnov; Dmitry Konovalov; Irina Veretennikova; Aleksander Pestov; Viktoria Osipova (Fracture and Structural Integrity)
The paper studies the adhesive strength of aluminum alloy specimens bonded with the use of an epoxy adhesive, under the tensile-shear stress state, depending on the testing temperature. Tension of modified Arcan specimens with load angles of 0, 22.5, 45, 67.5, and 90 with respect to the plane of adhesion is chosen as the experimental method. Experiments were performed at temperatures of -50, +23, and +50 ?. The analysis of the obtained results yields a linear fracture criterion and a fracture locus for the adhesive failure strain energy density, which takes into account the ratio of the elastic properties of the adhesive to those of the substrate. The region bounded by the fracture loci of adhesive strength and ultimate strain energy density determines the conditions for the safe loading of the bonded assembly in terms of the energy and force criteria of adhesive failure. The proposed fracture loci can be used, preferably simultaneously, to estimate the in-service strength and reliability of adhesively bonded assemblies.